TEK/Tie2 Is a Novel Gene Involved in Endoplasmic Reticulum Stress - Toru Hosoi; Taiji Tamubo; Naohiro Horie; Yasunobu Okuma; Yasuyuki Nomura; Koichiro Ozawa (Elsevier, 2010)
Endoplasmic reticulum (ER) stress has been implicated in the pathogenesis of diseases such as neurodegenerative disease. In the present study, we established the ER stress-resistant SH-SY5Y cell line, and through microarray analysis, we found that TEK/Tie2 expression is up-regulated in this cell line. Moreover, we found that TEK/Tie2 expression was markedly decreased in ER-stressed cells. The effect was time-dependent (2 - 24 h), which began to decrease from 2-h time point. Our findings suggest that TEK/Tie2 expression is involved in cell survival, whereas when severe ER stress occurs, TEK/Tie2 expression is down-regulated, resulting in cell death. Keywords:: neurodegenerative disease, Akt, microarray